Reducing fractures in diamond-milled lithium metasilicate/disilicate glass-ceramics (LMGC/LDGC) by ultrasonic vibration-assisted machining - Juri, Afifah Z.; Lei, Xiangtian; Dudley, James; Lohbauer, Ulrich; De Souza, Grace M.; Nakanishi, Yoshitaka; Yin, Ling (Journal of the Mechanical Behavior of Biomedical Materials, 2025)
Digital CAD/CAM milling of aesthetic glass-ceramics in dental restorations induces extensive surface damage to the materials, jeopardising the quality of the restorations. This study aimed to reduce fractures in lithium metasilicate and disilicate glass-ceramics (LMGC and LDGC) induced by novel ultrasonic vibration-assisted machining for improved surface quality. Ultrasonic vibration-assisted machining of LMGC and LDGC was performed using a digital high-speed ultrasonic milling machine. Machining-induced surface fractures were quantitatively assessed in terms of 3D surface height, spatial, and hybrid parameters as a function of vibration amplitudes using a 3D white light profilometer. Damage morphologies were examined using scanning electron microscopy (SEM). Machining-induced surface fractures significantly depended on material microstructures, mechanical properties associated with brittleness and machinability indices, and ultrasonic machining vibration amplitudes. Higher brittleness indexed LMGC produced more surface damage than LDGC. Thus, LMGC surfaces had significantly higher 3D surface height, spatial, and hybrid parameters than LDGC, except texture aspect ratios. Brittle fracture dominated all material removal but ultrasonic machining at an optimized vibration amplitude of 3 μm promoted localized ductile deformation in LMGC and LDGC, and significantly improved the surface quality. Ultrasonic vibration-assisted machining at the optimized vibration amplitude enabled the surface quality improvement for both LMGC and LDGC. Further, one-step (direct) machining of LDGC can be approached for rapid high-quality ceramic restorations, replacing the two-step procedure for LMGC and saving the fabrication time.
CRIS-Team Scopus Importer:2025-05-09
Keywords: Damage morphology; Glass-ceramics; Material removal mechanisms; Surface roughness; Ultrasonic vibration-assisted machining